The spatio-temporal evolution of leishmaniasis in the province of Essaouira - Benkhira, Said; Boudebouch, Najma; Benazzouz, Bouchra (Frontiers in Epidemiology, 2024)
Leishmaniasis is a highly prevalent neglected tropical disease. It represents a significant public health concern in northern Africa, particularly in Morocco. To assess the extent of the disease at the provincial level, as well as the temporal evolution of CL cases and their geographic distribution. 834 cases of cutaneous leishmaniasis (CL) diagnosed positive by the hygiene and health laboratory of the health delegation of the province of Essaouira during the period from January 1 st , 2014 to December 31 st , 2023. Among the 57 communes of the province, three are hyper-endemic and represent the main foci of LC; Elhanchan, Had Draa, Smimou with 66.42% of cases. Other communes with significant increases include Aguerd, with 15.6% of cases, an incidence peak of 279.7 per 100,00.0 in 2022, and Bizdad, 11.8% with an average incidence of 41.1 per 100,000. The transmission of the parasitosis continues to spread to create new outbreaks each year and reach 25 municipalities in the province which have experienced at least one positive case in 2023. Two new outbreaks appeared after 2018 in Sidi Kaouki (5% of cases) and Tidzi (5.6%). The temporal analysis shows a significant rise in cases over time, with an annual average of 83 cases. The trend paused during the COVID-19 lockdown but resumed exponentially, peaking in 2023. The overall incidence in the province increased from 11.1 per 100,000 in 2015 to 40.3 per 100,000 in 2023, with a significant rise over the study period (p < 0.001). The average incidence during this time was 18.32 per 100,000, showing considerable variability across different years. The spread of cutaneous leishmaniasis in the province of Essaouira is multifactorial and results from the complex interaction between vectors, parasites, the environment, and human behaviors. A better understanding of these factors is essential to developing effective disease prevention and controlling strategies.